Literature Review on the Role of School Principals in the Society 5.0: Strategies and Future Challenges - Soleman Saidi; Eny Suryowati; Ummu Sholihah; Fatqurhohman Fatqurhohman (Review of Education, Science, and Technology, 2025)
This study explores the role of school principals in the era of Society 5.0, emphasizing strategies and challenges in leading education within the VUCA context. Using a library research method, the study reviews relevant scientific literature from books, journal articles, conference proceedings, research reports, and official documents published within the last decade. The analysis highlights that principals are required to act as adaptive and innovative leaders who integrate technological advancement with strong character education. Effective leadership in this context must be holistic and contextual, bridging educational policies with classroom realities, addressing infrastructure disparities, and fostering collaborative, human-centered learning cultures. Furthermore, the findings reveal that the success of school leadership in Society 5.0 cannot be solely measured by the sophistication of technology, but by its effectiveness in creating inclusive, adaptive, and sustainable learning ecosystems. Future research opportunities remain wide open, particularly longitudinal and empirical studies on dialogical and collaborative leadership, as well as the development of learning communities. This study contributes both theoretically and practically by offering insights into leadership models that align with the demands of Society 5.0, while also providing direction for future educational leadership research.